Paham Eskatologi dalam Injil Yohanes dan Makna Temporalnya - Tafaib, Gratiana (Jurnal Orientasi Baru, 2014)
The gospel of John offers new ideas and meanings about eschatology. One of those newnesses is about the temporal meaning of the eschaton. This paper will discuss the John’s presentation on the eschatology and its meaning by analyzing some particular passages in the Gospel of John. The meaning of eschatology is found in public service and preachings of Jesus. Each person who believes in Jesus and lives in His way reach eternal life.